Systematization of methods for NC measuring machines programming - Vasić, Siniša; Stankov, Jelena (Journal of Production Engineering, 1990)
Coordinate Measuring Machines (OTU) represent the complex metrological systems with partial or full programming and automatization measuring processes, processing and in-dictation of measuring results. Regardless of the fact that they appeared not earlier than sixty, their rapidly development and intensive diffusion on industry practice is evedent. In this relatively short time, the several generations and many types of these contemporary metrological systems have been developed - from manual, controlling all14 to DPIC am. Intensive development of 001 is bring about by Knowlagent that usage of CVM makes possible solving almost all the measuring tasks appear in practice. Their usage allows measuring of dimensions, forms, location, and surface quality. Because of the effective realization of all measuring tasks different procedures of COI programming are developed. There are different approaches, terminologies and classification in connection with programming methods. The paper represents an attempt of classification, on the base of all inclusive analyze of literature information, programing methods for numerical controlled CHM. The short review of basic characteristics of these methods is presented as well.